Altered Immunity and Microbial Dysbiosis in Aged Individuals With Long-Term Controlled HIV Infection - Rhoades, Nicholas; Mendoza, Norma; Jankeel, Allen; Sureshchandra, Suhas; Alvarez, Alexander D.; Doratt, Brianna; Heidari, Omeid; Hagan, Rod; Brown, Brandon; Scheibel, Steven; Marbley, Theodore; Taylor, Jeff; et al. (Frontiers in Immunology, 2019)
The introduction of highly active antiretroviral therapy (HAART) has resulted in a significant increase in life expectancy for HIV patients. Indeed, in 2015, 45% of the 1.2 million HIV+ individuals in the United States were 55 years of age or older. Despite the improvement in diagnosis and treatments of HIV infection, geriatric HIV+ patients suffer from higher incidence of comorbidities compared to age-matched HIV- individuals. Both chronic inflammation and dysbiosis of the gut microbiome are believed to be major contributors to this phenomenon, however carefully controlled studies investigating the impact of long-term (> 10 years) controlled HIV (LTC-HIV) infection are lacking. To address this question, we profiled circulating immune cells, immune mediators, and the gut microbiome from elderly (> or equal to 55 years old) HIV+ and age-matched HIV- gay men living in the greater Palm Springs area. HIV+ individuals had lower frequency of circulating monocytes and CD4+ T-cells, and increased frequency CD8+ T-cells. Moreover, levels of systemic INFγ and several growth factors were increased while levels of IL-2 and several chemokines were reduced. Upon stimulation, immune cells from LTC-HIV individuals produced higher levels of pro-inflammatory cytokines. Last but not least, the gut microbiome of HIV+ individuals was enriched in bacterial taxa typically found in the oral cavity suggestive of loss of compartmentalization, while levels of beneficial butyrate producing taxa were reduced. Additionally, prevalence of Prevotella negatively correlated with CD4+ T-cells numbers in HIV+ individuals. These results indicate that despite long-term adherence and undetectable viral loads, long-term HIV infection results in significant shifts in immune cells frequencies and microbial communities.